Towards Tawang Station Area as Smart Urban Railway Space - Nurma Mediasri Huwaida; Agung Nugroho; Reivandy Christal Joenso (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2020)
The purpose of this research is to analyze the possibility of implementing Smart Urban Railway Space concept in the development of Semarang Tawang Station area which is one of the entrance gates of Semarang tourists and has a high historical value. The area of Tawang station becomes an integral part of Semarang Old Town because of its adjacent location. This attachment is one potential that can be considered to grow the activity of the area into a tourism area and a business center. Increasing number of visitors can cause overcrowding. The crowded situation of visitors caused the lack of circulation so that the need for redesigning Tawang station area. A station area (public transportation) must be able to adapt to the environment and function needs for the visitor. Smart city design is about rethinking infrastructure, buildings and facilities as well as other infrastructure integrated to form smart cities and smart urban space. Smart Urban railway space is a concept that integrates an architectural building with the surrounding open space. It is hoped that this concept can parse overcrowding and make the area of Tawang station a tourism area. Methods used are qualitative methods with a rationalistic approach. The result of this research is a recommendation of the Smart Urban Railway Space concept at Tawang station area which is expected to parse the overcrowding problem that occurred.